Zakat in Poverty Alleviation and Improving The Community’s Financial Economy: The Role of Empowerement Human Resources - A. Nur Fitrianti; Andi Arifwangsa Adiningrat; Sri Wahyuni; Idrawahyuni Idrawahyuni; Warda Warda (Yayasan Riset dan Pengembangan Intelektual, 2024)
Poverty occurs due to several factors, including low education, low work productivity, minimum wage, human development index, unemployment and other factors. This research aims to determine the role of human resources in the distribution of zakat in alleviating poverty, and to determine zakat in alleviating poverty and improving the community financial economy through community empowerment. The research approach uses qualitative descriptive analysis. The data collection technique was carried out by distributing questionnaires, interviewing informants and drawing on journal articles related to the research variables. The qualitative steps are carried out by reduction, presentation and drawing conclusions. The research results show that (1). The role of human resources in distributing zakat is quite effective but not yet optimal, (2). Zakat in alleviating poverty through community empowerment in the aspect of zakat in individual economic independence is categorized as effective even though it is not completely independent, and 3). Zakat which is managed using a human resource empowerment approach has great potential to improve the community's financial economy, although it is not yet optimal